CONSTRAINTS ENCOUNTERED BY THE FARMERS IN ACCESSING INSTITUTIONAL CREDIT IN HARYANA - Verma, Lucky; Suneja, Ajay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India relies heavily on agricultural sector, which employs over 55% of the population. The growth of this sector is crucial for the overall economy, providing livelihoods and supporting related industries. This study tries to access the various challenges that are faced by the farmers while getting institutional credit. This study based on collected data from 363 farmers in 8 districts of Haryana state. The present study applied exploratory factor analysis, and identified seven factors that contained 63.423% of the total variance, with a KMO value of 0.884. The findings highlight several critical challenges faced by farmers in accessing institutional credit. These include complex procedural requirements, uncooperative attitudes of bank employees, and instances of discrimination. In addition, issues such as time consumption in processing applications, widespread illiteracy, and a lack of awareness about available credit facilities also pose significant barriers for farmers.